The Limits of Literary Historicism - Haddox, Thomas F. (Thomas Fredrick); Dunn, Allen (Book collections on Project MUSE., 2011)
The Limits of Literary Historicism is a collection of essays arguing that historicism, which has come to dominate the professional study of literature in recent decades, has become ossified. By drawing attention to the limits of historicism--its blind spots, overreach, and reluctance to acknowledge its commitments--this provocative new book seeks a clearer understanding of what historicism can and cannot teach us about literary narrative. Editors Allen Dunn and Thomas F. Haddox have gathered contributions from leading scholars that challenge the dominance of contemporary historicism. These pieces critique historicism as it is generally practiced, propose alternative historicist models that transcend mere formula, and suggest alternatives to historicism altogether. The volume begins with the editors' extended introduction, "The Enigma of Critical Distance; or, Why Historicists Need Convictions," and then is divided into three sections: "The Limits of Historicism," "Engagements with History," and "Alternatives to History." Defying convention, The Limits of Literary Historicism shakes up established modes to move beyond the claustrophobic analyses of contemporary historicism and to ask larger questions that envision more fulfilling and more responsible possibilities in the practice of literary scholarship.